2019
DOI: 10.3389/fphar.2019.01398
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metabolic Dysfunction in Early Neuropsychiatric Symptoms of Dementia

Abstract: Neuropsychiatric symptoms (NPS) including behavioral and psychiatric symptoms are common in the dementia stages of Alzheimer's disease (AD) and are associated with poorer outcomes in cognition, functional states, quality of life, and accelerated progression to severe dementia or death. NPS are also increasingly observed in the mild cognitive impairment stage of AD and may predict incipient dementia. As such, there is an emerging conceptual framework, which support NPS as early non-cognitive symptoms of dementi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 82 publications
2
10
0
Order By: Relevance
“…Among these trajectories, only the increasing trajectory was associated with a higher risk of dementia compared to the low trajectory. The high risk of dementia observed only during the increasing trajectory of depression in our study and in the Rotterdam study further supports the prodromal hypothesis, which suggests that depressive symptoms during old age possibly represent a prodrome or an early stage of dementia (Mirza et al, 2016;Ng et al, 2019). However, previous studies showed that chronic SSD is associated with the atrophy rates in the frontal and anterior cingulate cortices but not with the atrophy rates in typical AD-related regions such as the hippocampus and entorhinal cortex.…”
Section: Discussionsupporting
confidence: 85%
“…Among these trajectories, only the increasing trajectory was associated with a higher risk of dementia compared to the low trajectory. The high risk of dementia observed only during the increasing trajectory of depression in our study and in the Rotterdam study further supports the prodromal hypothesis, which suggests that depressive symptoms during old age possibly represent a prodrome or an early stage of dementia (Mirza et al, 2016;Ng et al, 2019). However, previous studies showed that chronic SSD is associated with the atrophy rates in the frontal and anterior cingulate cortices but not with the atrophy rates in typical AD-related regions such as the hippocampus and entorhinal cortex.…”
Section: Discussionsupporting
confidence: 85%
“…The evidence for the associations between neurodegeneration and NPS in preclinical AD is inconsistent, which may be due to the small number of studies and the variability of biomarkers studied. However, studies have extensively evaluated the neuroanatomical and metabolic correlates of NPS in the MCI and dementia stages of AD, suggesting that the NPS are associated with neurodegeneration of specific neural networks in AD [69][70][71]. Therefore, it may not be surprising to observe a lack of an association between NPS and neurodegeneration in preclinical AD.…”
Section: Discussionmentioning
confidence: 99%
“…The development of AD biomarkers and neuroimaging methods has further advanced the understanding of the mechanisms leading to NPS in AD. In these reviews, brain networks/circuits that are involved in agitation, apathy and delusions [71], neuropathology, neurotransmitter, neuroimaging, ApoE genotype, inflammation, and clusterin biomarkers associated with agitation and aggression in AD [79], and metabolic dysfunctions associated with NPS in the AD continuum [70], have been discussed. Most recently, a systematic review has further shown inconsistent associations between AT(N) biomarkers and NPS such as depression, anxiety, apathy, agitation, irritability and night-time behavioral disturbances in MCI and AD dementia [44].…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological process of AD begins years before the diagnosis of clinical dementia 3 . Recent research shows that neuropsychiatric symptoms (NPS) or mild behavioural impairment (MBI) could be early manifestations of neurodegenerative disease 4–12 …”
Section: Introductionmentioning
confidence: 99%